MEDIA NEEDS ANALYSIS OF LEARNING MEDIA IN 5TH GRADE TIK SUBJECTS AT STUDENT ONE ISLAMIC PRIMARY SCHOOL: Analisis Kebutuhan Media Pembelajaran Pada Mata Pelajaran TIK Kelas 5 Di SD Islam Student One - Silmy, Iklany; Fatonah, Umi; Muhyidin Nurzaelani, Mohammad (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
ICT learning on the material of activating the computer in the right way is still abstract. One way to overcome this is to learn using learning media. However, the development of this media needs to adjust the needs of students so that a needs analysis is needed. This study aims to analyze the needs in the development of learning media needed by students in grade V of SD Islam Student One. This research is a qualitative research. The participants were students and 6th-grade teachers of SD Islam Student One. The data collection techniques in this study were interviews and observations. The results showed that the learning media needed by students is Articulate Storyline learning media which is able to visualize real images and requires learning media that is not monotonous so that students take an active role in learning activities.